Evaluation of Serum Cortisol and Thyroid Hormone Levels in Patients with Major Depressive Disorder - Sibgha Usman, Haleema Hammad, Yamna Fatima, Ali Hassan, Samra Naeem, Nargis Haider, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Serum cortisol and thyroid hormone levels were examined in patients diagnosed with majordepressive disorder (MDD) to evaluate their potential role as endocrine biomarkers. A case-controlstudy enrolled treatment-naïve adults with MDD and matched healthy controls.